Rensch's rule is not verifiedin melanopline grasshoppers (Acrididae) - Bidau, Claudio Juan (2013)
Sexual size dimorphism (SSD) is almost universal in animals. Rensch?s rule proposes that SSD increases with increasing average body size in taxa where males are larger than females (male- biased SSD; MBSSD) and decreases when females are larger (femalebiased SSD; FBSSD). Although it was proposed thatboth patterns are part of the same evolutionary trend, there is more evidence for Rensch?s rule in the first case. We analyzed SSD in the acridid subfamily Melanoplinae ina sample of 718 species and subspecies covering all tribes and representative genera. As in all Orthopera, SSD is female-biased. Body length was used as a proxy for body size. Mean body size within the subfamily varied between 9 and 34.5 mm in males (N= 812) and 12.75 and 44.0 mm in females (N= 735). Except for five species (0.7%) all taxa (from subfamily to subspecies) showed moderate to strong FBSSD (mean= 1.27). The lowest SSD was observed in Melanoplus chumash(SSD= 1.01), and the highest in Phaedrotettix aptera coquinae(SSD= 1.83). To test Rensch?s rule we performed reduced major axis (RMA) regressions between log10 (male body length) and log10 (female body length). In no case RMA slopes were significantly higher than 1.0 which would signal Rensch?s rule. Thus, Melanoplinae representsa new case of FBSSD where Rensch?s rule is not verified. The proximatecauses of FBSSD and the non-occurrence of Rensch?s rule in the Orthoptera are discussed as well as the relationship between SSD patterns at the intra- and supraspecific levels.